ACADEMIC RESEARCH: ROLE OF AI IN SCHOLARLY PRACTICES - Bhat, Mohammad Sayid (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study investigated the role of AI tools in academic research pursued by scholars for their research work at the universities of Jammu and Kashmir. The study further intended to explore the diverse AI tools used in content generation and evaluate their efficiency in research paper/dissertation/thesis writing. Preliminary findings revealed that most respondents utilise the AI tool Grammarly for grammar checking and clarity. The study focused on identifying the AI tools researchers use for effective writing. A questionnaire (Likert Scale with 03 alternatives: Agree to Disagree) developed by M. Monika, V. Divyavarsini and C. Suganthan with 40 items was employed to assess variables such as academic writing, content generation, paraphrasing, academic referencing & citation, and proofreading and grammar check. The questionnaire was sent online (via email and social media) in a Google Form to research scholars registered in various universities in Jammu and Kashmir. In this study, 342 research scholars participated. Data collected were analysed using descriptive statistics, which included frequency analysis, percentages, and graphical representation. Furthermore, most respondents acknowledged that AI tools facilitate the writing process, mainly simplifying the referencing style. While recognising the benefits of AI tools, researchers emphasised the importance of critical evaluation and the need for human judgment. They indicated that AI tools are used strategically for tasks such as paraphrasing, grammar checking, and citation management rather than as a complete replacement for human authorship.